Heterodyne mixing of millimetre electromagnetic waves and sub-THz sound in a semiconductor device - Heywood, Sarah L.; Glavin, Boris A.; Beardsley, R.P.; Akimov, Andrey V.; Carr, Michael W.; Norman, James; Norton, Philip C.; Prime, Brian; Priestley, Nigel; Kent, Anthony J. (Nature Publishing Group, 2016)
We demonstrate heterodyne mixing of a 94 GHz millimetre wave photonic signal, supplied by a Gunn diode oscillator, with coherent acoustic waves of frequency ~ 100 GHz, generated by pulsed laser excitation of a semiconductor surface. The mixing takes place in a millimetre wave Schottky diode, and the intermediate frequency electrical signal is in the 1 – 12 GHz range. The mixing process preserves all the spectral content in the acoustic signal that falls within the intermediate frequency bandwidth. Therefore this technique may find application in high-frequency acoustic spectroscopy measurements, exploiting the nanometre wavelength of sub-THz sound. The result also points the way to exploiting acoustoelectric effects in photonic devices working at sub-THz and THz frequencies, which could provide functionalities at these frequencies, e.g. acoustic wave filtering, that are currently in widespread use at lower (GHz) frequencies.